(untitled) (Orfeu, 2025)
This study investigates the intellectual affiliation of pre-service music teachers at three public universities in Minas Gerais, Brazil. The focus lies on analyzing their mastery of cognitive strategies and academic behaviors essential for academic success, based on Alain Coulon’s pedagogy of intellectual affiliation. Using an online Likert-scale questionnaire, the research assessed students’ academic practices and considered social markers such as family income and educational background. The findings reveal that, although students acknowledge the importance of these strategies, they have not yet fully mastered them, potentially due to their social profiles. This highlights the urgent need for pedagogical support to foster intellectual affiliation and underscores the faculty’s role in developing these skills beyond traditional curricular content. The study aims to contribute to the democratization of higher education by strengthening institutional and pedagogical policies that ensure retention and the successful training of future music educators.